Cut-off Value of HSPG for Early Marker of Plasma Leakage in Adult Dengue Patient - Settrin Chenderawasi; Rahajuningsih Dharma; Herdiman T. Pohan; Beti Ernawati Dewi; Rianto Setiabudy; Suhendro Suhendro; Aryati Aryati; Hardi Darmawan; Leonard Nainggolan; Agustin Iskandar (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Plasma leakage is a state of increased vascular permeability due to loss of interendothelial junction and focal adhesion. Endothelium glycocalyx plays a major role in the pathogenesis of plasma leakage. Proteoglycans glycocalyx consists of heparan sulfate (HSPG) around 50-90%. Plasma leakage in dengue infection can be fatal and early detection is essential. This study aimed to determine the optimal cut-off value of HSPG levels for early marker of plasma leakage in dengue infection. The study was a retrospective cohort study as a part of the Community Based Dengue Study of the Faculty of Medicine, University of Indonesia, which was conducted between February 2010 and January 2011. Subjects were recruited by consecutive sampling. Dengue infection was confirmed by conventional PCR serotyping. Subjects were categorized into 2 groups, i.e. those with and without plasma leakage. Plasma leakage was confirmed by hemoconcentration or hypoalbuminemia or USG results. The level of HSPG was measured using the ELISA method from the first until the third day of the hospital admission. A total of 40 subjects were involved in this study, consisting of 21 with leakage and 19 without leakage. The optimal cut-off level of HSPG as a marker of early plasma leakage in dengue infection patients on the 1st day, 2nd day, and 3rd day was was 2179.73 pg/mL, 2538.66 pg/mL, and 1294.06 pg/mL, respectively. HSPG could as an early marker of plasma leakage in dengue infection with an optimal cut-off value for each of the first 3 days of the patient's fever. A pediatric study was recommended to obtain the optimal cut-off value for HSPG.